Focus on the heterogeneity of amyotrophic lateral sclerosis - Bendotti, Caterina; Bonetto, Valentina; Pupillo, Elisabetta; Logroscino, Giancarlo; Al-Chalabi, Ammar; Lunetta, Christian; Riva, Nilo; Mora, Gabriela; Lauria, Giuseppe; Weishaupt, Jochen H.; Agosta, Federica; Malaspina, Andrea; et al. (Amyotrophic lateral sclerosis & frontotemporal degeneration, 2020)
The clinical manifestations of amyotrophic lateral sclerosis (ALS) are variable in terms of age at disease onset, site of onset, progression of symptoms, motor neuron involvement, and the occurrence of cognitive and behavioral changes. Genetic background is a key determinant of the ALS phenotype. The mortality of the disease also varies with the ancestral origin of the affected population and environmental factors are likely to be associated with ALS at least within some cohorts. Disease heterogeneity is likely underpinned by the presence of different pathogenic mechanisms. A variety of ALS animal models can be informative about the heterogeneity of the neuropathological or genetic aspects of the disease and can support the development of new therapeutic intervention. Evolving biomarkers can contribute to the identification of differing genotypes and phenotypes, and can be used to explore whether genotypic and phenotypic differences in animal models might help to provide a better definition of the heterogeneity of ALS in humans. These include neurofilaments, peripheral blood mononuclear cells, extracellular vesicles, microRNA and imaging findings. These biomarkers might predict not only the development of the disease, but also the variability in progression, although robust validation is required. A promising area of progress in modeling the heterogeneity of human ALS is represented by the use of human induced pluripotent stem cell (iPSCs)-derived motor neurons. Although the translational value of iPSCs remains unclear, this model is attractive in the perspective of replicating the heterogeneity of sporadic ALS as a first step toward a personalized medicine strategy.